2010
DOI: 10.1111/j.1440-1819.2010.02085.x
|View full text |Cite
|
Sign up to set email alerts
|

Posterior orbitofrontal sulcogyral pattern associated with orbitofrontal cortex volume reduction and anxiety trait in panic disorder

Abstract: Aims:  The posterior region of the orbitofrontal cortex (OFC), which forms its sulcogyral pattern during neurodevelopment, receives multisensory inputs. The purpose of the present study was to assess the relationship between posterior OFC sulcogyral pattern and OFC volume difference in patients with panic disorder. Methods:  The anatomical pattern of the posterior orbital sulcus (POS) was classified into three subtypes (absent POS, single POS, double POS) using 3‐D high‐spatial resolution magnetic resonance im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 31 publications
4
29
0
1
Order By: Relevance
“…Voxel-based morphometry studies have identified reduced gray matter volume in the right orbito-frontal cortex and right inferior frontal gyrus in patients with panic disorder. 10 The main limitation of this study is that the assessment of PSA was made only once, at the 3-month follow-up. Patients who could not give consent because of dementia or aphasiaassociated left-side infarcts were also excluded.…”
Section: Discussionmentioning
confidence: 97%
“…Voxel-based morphometry studies have identified reduced gray matter volume in the right orbito-frontal cortex and right inferior frontal gyrus in patients with panic disorder. 10 The main limitation of this study is that the assessment of PSA was made only once, at the 3-month follow-up. Patients who could not give consent because of dementia or aphasiaassociated left-side infarcts were also excluded.…”
Section: Discussionmentioning
confidence: 97%
“…Besides healthy individuals, structural abnormalities in the OFC have been found in patients with affective (Bremner et al, 2002;Lacerda et al, 2004) and anxiety disorders (Hayano et al, 2009;Roppongi et al, 2010;Sobanski et al, 2010). A reduced regional brain volume in the OFC has been related to reduced gyrification and anxiety-related traits in panic disorder (Roppongi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A reduced regional brain volume in the OFC has been related to reduced gyrification and anxiety-related traits in panic disorder (Roppongi et al, 2010). Roppongi et al suggested that given the lack of differences in gyrification between patients with panic disorders and healthy controls, anxiety-related volume changes in the OFC could be associated with neurodevelopment in these patients rather than with other factors associated with their clinical condition, such as aversive life events.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, vmPFC dysfunction is observed in many different clinical conditions marked by emotional disturbances such as panic disorder, bipolar disorder, substance abuse, and major depressive disorder (Alia-Klein et al, 2011;Altshuler et al, 2008;Lacerda et al, 2004;Roppongi et al, 2010;Tanabe et al, 2009). Therefore, vmPFC dysfunctionality is not unique to secondary psychopathy but could be the neural substrate through which the comorbidity between a variety of clinical conditions marked by emotional dysregulation can be explained.…”
Section: Accepted Manuscriptmentioning
confidence: 99%